Determinants of bank lending performance - Ralf Ewert; Gerald Schenk (Goethe University Frankfurt, Center for Financial Studies (CFS), 1998)
During the last years the lending business has come under considerable competitive pressure and bank managers often express concern regarding its profitability vis-a-vis other activities. This paper tries to empirically identify factors that are able to explain the financial performance of bank lending activities. The analysis is based on the CFS-data-set that has been collected in 1997 from 200 medium-sized firms. Two regressions are performed: The first is directed towards relationships between the interest rate premiums and various determining factors, the second aims at detecting relationships between those factors and the occurrence of several types of problems during the course of a credit engagement. Furthermore, the results of both regressions are used to test theoretical hypotheses regarding the impact of certain parameters on credit terms and distress probabilities. The findings are somewhat 'puzzling': First, the rating is not as significant as expected. Second, credit contracts seem to be priced lower for situations with greater risks. Finally, the results do not fully support any of three hypotheses that are often advanced to describe the role of collateral and covenants in credit contracts.
urn:nbn:de:hebis:30-9395
Keywords: G21; G32; G33; 330; banking; cost of capital; distress prediction; finance